Direct Percutaneous Embolization of Peristomal Ileostomy Varices in an Emergency Setting - William Ryan; Farouk Dako; Gary Cohen; David Pryluck; Joseph Panaro; Emily Cuthbertson; Dmitry Niman (Case Reports in Radiology)
Patients with liver disease and portal hypertension who have had surgical formation of an abdominal stoma are at risk of developing peristomal varices. These varices have a predilection for bleeding. Ideally, portal decompression via TIPS procedure is performed, with or without direct embolization of the bleeding varix. When TIPS is not an appropriate option due to significant liver disease and hepatic encephalopathy there are other approaches to treat peristomal variceal hemorrhage. We report the embolization of such a varix via direct percutaneous puncture under ultrasound guidance when portal decompression was not an appropriate option.